PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI BUDIDAYA JAMUR MERANG DENGAN PEMANFAATAN MEDIA KARDUS - Silvia Anzitha; Muhammad Jamil (Global Science Society, 2020)
To contribute to the real work of Higher Education through the implementation of Community Service activities, one of the potential locations for improving mushroom cultivation technology with the use of cardboard media is a form of utilization of useful local resources, which has been a waste that has not been used. useful and very disturbing environmental sustainability. The chosen location is Meurandeh Teungoh Village, Langsa Lama District, Langsa City. The use, benefits and ways of applying straw mushroom cultivation technology to the community or farmers, farmers are expected to be interested in the technology so that it can be applied to mushroom cultivation business in the future. The introduction or socialization of the method of utilizing cardboard media in the cultivation of straw mushrooms is believed to be easily understood by the community or farmers as participants, because the community will be trained in how to conduct direct demonstrations between the program implementers (proposers) with the community as participants of community service activities.